(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article presents the structural and functional features of the development of the digestive organs in early postnatal ontogenesis. It is shown that the digestive organs of the newborn are still unformed, therefore the baby is immature. The final formation of the organs and systems of digestion occurred in the lactotrophic and subsequently mixed periods of feeding.